29 Leadership Secrets from Jack Welch - Robert Slater (McGraw-Hill, 2003)
Jack Welch, the long-time Chairman and CEO of General Electric, has been hailed as the greatest business leader of our era and deservedly so. It was Welch who headed GE from April 1981 to September 2001 and who pioneered some of the most important business strategies of the past two decades. We now take these strategies for granted as part of the way American business is done: restructuring, the emphasis on being number one or number two, making quality a top priority (through his Six Sigma initiative), and so on. Moreover, Welch, unlike most other business leaders, created a tightly woven, carefully scripted business philosophy that provided brief, crisp guidelines for every aspect of business. Welch’s main leadership secrets, spelled out in this book, continue to resonate throughout the business world. Few other business leaders have articulated how to achieve maximum performance with such clarity and forthrightness. Before Welch took over at GE, the business world had revered large bureaucracies as critical for close monitoring of personnel; it had placed great faith in a command-and-control management system, encouraging senior management to overmanage; it had allowed the employee to attain a protected status by being assured of a job for life. Jack Welch punctured holes in each of these notions. His legacy is that he has forever altered these myths and has inspired managers of corporations around the world to behave far differently: Bureaucracies are much smaller, with fewer management layers; managers manage much less, delegating far greater authority to empowered employees; the right to a job for life is no longer guaranteed as management runs much tighter, more productive ships. Welch’s performance at General Electric lent mighty credence to his ideas: When he assumed the post of Chairman and CEO of GE, the company had annual sales of $25 billion and earnings of $1.5 billion, with a $12 billion market value, tenth best among Copyright 2003 by The McGraw-Hill Companies, Inc, Click Here for Terms of Use. viii 29 Leadership Secrets from Jack Welch American public companies. In 2000, the year before Welch retired, GE had $129.9 billion in revenues; and $12.7 billion in earnings. In 2001, GE’s revenues stood at $125.9 billion; and earnings rose to $14.1 billion. From 1993 until the summer of 1998, GE was America’s market cap leader. Under Welch, the company reached a high of $598 billion in market cap (but settled in at about $400 billion during Welch’s final years as CEO). Fortune magazine selected GE as ‘‘America’s Greatest Wealth Creator’’ from 1998 to 2000. Anyone in business, from the most powerful corporate managers to the hourly factory worker, has much to learn from Jack Welch and his ideas. Studying his leadership secrets tells us what American business was once like, and outlines how the tactics he pioneered have changed business for the better in so many ways.